Narratives of tampering in the earliest commentaries on the Qurʻan - Nickel, Gordon D. (History of Christian-Muslim relations, 2011)
Shedding light on a theme which affects Muslim-Christian conversation to the present day, this book describes the earliest extant interpretations of the Qur'?n's ""tampering"" verses which have been used to support the Muslim accusation of the corruption of pre-Qur'?nic scriptures.